Type 2N von Willebrand disease due to compound heterozygosity for R854Q and a novel R763G mutation at the cleavage site of von Willebrand factor propeptide - Hilbert, Lysiane; Nurden, Paquita; Caron, Claudine; Nurden, Alan T.; Goudemand, Jenny; Meyer, Dominique; Fressinaud, Edith; Mazurier, Claudine; and the INSERM Network on Molecular Abnormalities in von Willebrand Disease (Thrombosis and Haemostasis, 2006)
Type 2N von Willebrand disease (VWD) is characterized by a markedly decreased affinity of von Willebrand factor (VWF) for factorVIII (FVIII) and is caused by mutations in the D’ or D3 domain of mature VWF. We now report a French patient with an atypical 2N VWD phenotype associating FVIII deficiency with plasmaVWF unable to bind FVIII (undetectableVWF:FVIIIB) but with an abnormal multimeric profile. This patient is heterozygous for both the frequent R854Q type 2NVWD mutation and a novel R763G mutation at the cleavage site betweenVWF propeptide and mature VWF. Four children of the patient displayed moderately decreased VWF:FVIIIB of plasma VWF and were heterozygous for either the R763G or the R854Q mutation. Children with the R763G mutation displayed the same abnormal multimeric profile as their father. Recombinant VWF (rVWF) expression studies performed in COS-7 cells showed that the R763G mutation subtly affects its multimeric profile and dramatically impairs its FVIII binding function. Furthermore, the characteristics of hybrid G763/Q854 rVWF resulting from cotransfection experiments were in agreement with the type 2N VWD diagnosis of the patient. We conclude that R763G is a new type 2N VWD mutation located in the VWF propeptide which alters the proteolytic processing of VWF and consequently its binding to FVIII.
Keywords: von Willebrand factor; von Willebrand disease; mutation; cleavage site